High cytotoxic T-lymphocyte-associated antigen 4 and phospho-Akt expression in tumor samples predicts poor clinical outcomes in ipilimumab-treated melanoma patients. Issue 1 (February 2017) - Chakravarti, Nitin; Ivan, Doina; Trinh, Van A.; Glitza, Isabella C.; Curry, Jonathan L.; Torres-Cabala, Carlos; Tetzlaff, Michael T.; Bassett, Roland L.; Prieto, Victor G.; Hwu, Wen-Jen
Abstract : Ipilimumab, a fully human monoclonal antibody against cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), is the first immune checkpoint inhibitor approved for the treatment of unresectable melanoma on the basis of its overall survival (OS) benefit. However, ipilimumab is associated with significant immune-related adverse events. We hypothesized that biomarker exploration of pretreatment tumor samples and correlation with clinical outcome would enable patient selection with an increased benefit/risk ratio for ipilimumab therapy. At the University of Texas MD Anderson Cancer Center, a total of 81 advanced melanoma patients were treated on the Ipilimumab Expanded Access Program from 2007 to 2008. Using immunohistochemistry, we analyzed the expression of immune checkpoint (CTLA-4, PD-1, PD-L1) and Akt-pathway proteins in formalin-fixed tumor tissue. Associations between these biomarkers and progression-free survival (PFS) and OS were analyzed with univariate and multivariate Cox proportional-hazards models. There was a significant correlation between high CTLA-4 protein expression levels in tumor cells and risk of death ( P =0.02) and decreased PFS ( P =0.023). In addition, high expression of CTLA-4 in peritumoral lymphocytes correlated with poor OS ( P =0.023). In multivariate analysis, patients with high CTLA-4 and phospho-Akt (p-Akt) expression correlated with poor OS (log-rank test, P =0.039) and PFS (log-rank test, P =0.014). High levels of CTLA-4 and p-Akt expression in pretreatment tumor cells in melanoma patients were associated with poor clinical outcomes. Immunohistochemistry analysis of CTLA-4 and p-Akt in pretreatment tumor samples provides useful biomarkers that may enable improved patient selection for ipilimumab therapy. Prospective clinical studies are warranted to investigate the predictive value of these biomarkers.